Techniques of fragile renal organoids transplantation in mice - Matsumoto,Naoto (2021)
ABSTRACT Purpose: This study aimed to develop a microsurgical technique to transplant extremely fragile renal organoids in vivo, created by in-vitro reaggregation of metanephros from fetal mice. These organoids in reaggregation and development were examined histologically after transplantation under the renal capsule. Methods: Initially, metanephros from fetal mice were enzymatically treated to form single cells, and spheroids were generated in vitro. Under a microscope, the renal capsule was detached to avoid bleeding, and the outer cylinder of the indwelling needle was inserted to detach the renal parenchyma from the renal capsule using water pressure. The reaggregated spheroid was aspirated from the culture plate using a syringe with an indwelling needle outer cylinder and carefully extruded under the capsule. Pathological analysis was performed to evaluate changes in reaggregated spheroids over time and the effects of co-culture of spinal cord and subcapsular implantation on maturation. Results: In vitro, the formation of luminal structures became clearer on day 5. These fragile organoids were successfully implanted without tissue crapes under the renal capsule and formed glomerular. The effect of spinal cord co-transplant was not obvious histrionically. Conclusions: A simple and easy method to transplant fragile spheroids and renal under the renal capsule without damage was developed.